Diffusion-weighted MR imaging of thyroid nodules - Bozgeyik, Zulkif; Coskun, Sonay; Dagli, A. Ferda; Ozkan, Yusuf; Sahpaz, Fatih; Ogur, Erkin (Springer, 2009)
Introduction The purpose of our study was to determine the diagnostic role of diffusion-weighted imaging (DWI) in the differentiating of malignant and benign thyroid nodules by using fine needle aspiration biopsy cytology criteria as a reference standard. The apparent diffusion coefficient (ADC) values of the normal-looking thyroid parenchyma were also evaluated both in normal patients and in patients with nodules. Methods Between March 2007 and February 2008, 76 consecutive patients with ultrasound-diagnosed thyroid nodules and 20 healthy subjects underwent diffusion-weighted MR imaging by using single-shot spin echo, echo planar imaging. A total of 93 nodules were included in the study using the following b factors 100, 200, and 300 mm(2)/s. ADC values of thyroid nodules and normal area in all subjects were calculated and compared using suitable statistical analysis. Results Mean ADC values for malignant and benign nodules were 0: 96 +/- 0: 65 X 10(-3) and 3.06 +/- 0.71 X 10(-3) mm(2) / s for b-100 factor, 0.56 +/- 0.43 X 10(-3) and 1.80 +/- 0.60 X 10(-3) mm(2) / s for b-200, and 0.30 +/- 0.20 X 10(-3) and 1.15 +/- 0.43 X 10(-3) mm(2) / s, for b-300, respectively. Mean ADC values of malignant nodules were lower than benign nodules. There were significant differences in ADC values between benign and malignant nodules. ADC values among normal-appearing thyroid parenchyma of patients and normal-appearing thyroid parenchyma of healthy subjects were insignificant at all b factors. Conclusion Benign nodules have higher ADC values than malignant ones. DWI may be helpful in differentiating malign and benign thyroid nodules.
Keywords: Diffusion-weighted MR imaging; DWI; Thyroid nodule; Fine needle aspiration biopsy